Arithmetic P Systems Based on Arithmetic Formula Tables. Issue 3 (1st July 2015) - Yang, Ruilong; Guo, Ping; Li, Jia; Gu, Ping
Abstract : Arithmetic operations are fundamental incomputing models. Novel arithmetic P systems are constructed to perform four basic operations: addition, subtraction, multiplication, division. The digits of decimal integers are directly put into hierarchical membranes, one digit one membrane, thus, the number of membranes is reduced and complexity is lowered. Core evolution rules are designed for single digit operations according to the arithmetic formula tables widely used by humans. Some examples are given to illustrate how to compute decimal integers in these P systems and the results indicates that these P systems can efficiently carry out arithmetic computations of integers.